A Study on Dental Hygiene and Career Maturity of Students Based on Alderfer’s ERG Theory - Yang-Keum Han; An-Na Yeo (치위생과학회지, 2021)
Background: This study aimed to investigate the effects of department satisfaction and career maturity on the perceived health status, relationship, and self-efficacy of dental hygiene college students based on Alderfer’s existence-relationship-growth theory. Methods: We obtained convenience samples of dental hygiene students in Daejeon and Chungnam areas; 241 questionnaires were collected from 250 persons considering the dropout rate and used for the final analysis except for 9 careless responses. The differences in perceived health status, relationship, self-efficacy, department satisfaction, and career maturity according to general characteristics were analyzed using a t-test, one-way analysis of variance and Pearson’s correlation coefficients. Moreover, structural equation modeling was performed to confirm the variables. GFI, AGFI,CFI, RMR, RMSEA, TLI, and NFI indices were calculated to verify the fitness of the path model. Results: There were significant differences in self-efficacy, department satisfaction, career maturity according to grade, and significant differences in academic performance for all variables except relationship. The school system also had a significant effect on department satisfaction. Perceived health status, relationship, self-efficacy, department satisfaction, and career maturity demonstrated statistically significant positive correlations (p＜0.05). The factors affecting department satisfaction were relationship and self-efficacy. The indirect and total effects of perceived health status and relationship on career maturity were not statistically significant; however, the indirect and total effects of self-efficacy on career maturity were statistically significant. Conclusion: It is necessary to develop teaching methods according to student management plans for dental hygiene by comprehensively perceived health status, relationship, and self-efficacy affecting department satisfaction and career maturity.